Randomized clinical trial of lightweight composite mesh for Lichtenstein inguinal hernia repair - Post, Stefan; Weiß, Birgit; Kensy, Mareike; Neufang, Thomas; Lorenz, Dietmar (The British journal of surgery, 2004)
Almost half the patients who undergo hernia repair with mesh report a feeling of stiffness and a foreign body in the groin. This study evaluated whether patients noticed any difference between lightweight and standard polypropylene mesh for the repair of inguinal hernia.Patients scheduled for elective repair of unilateral or bilateral, primary or recurrent inguinal hernia by the Lichtenstein technique were randomized to receive either a conventional densely woven polypropylene mesh (100-110 g/m2) or a lightweight composite multifilament mesh (polypropylene 27-30 g/m2). Quality of life was assessed using Short Form 36 before operation and 6 months after surgery. Pain was assessed by means of a visual analogue scale 2 days and 6 months after surgery. The primary outcome measure was the feeling of a foreign body in the groin at 6 months.Some 122 hernias were randomized; 117 were included in the analysis of perioperative data, and 106 were re-examined after 6 months. There were no differences between the treatment groups with respect to early and late surgical complications. Use of lightweight mesh was associated with significantly less pain on exercise after 6 months (P = 0·042). In addition, fewer patients reported the feeling of a foreign body after repair with lightweight mesh (17·2 versus 43·8 per cent with conventional mesh; P = 0·003). Quality of life was improved significantly at 6 months compared with the preoperative assessment, and there were no differences between the treatment groups.Lightweight polypropylene mesh may be preferable for Lichtenstein repair of inguinal hernia. Larger cohorts with longer follow-up are needed before it can be recommended for routine use.